The effect of BRICS trade relations on South Africa's growth - Adrino Mazenda (Economics and Econometrics Research Institute (EERI), 2016)
The article addressed the central issue on whether South Africa's joining of the BRICS has led to a sustainable growth as was envisaged. An econometric assessment was done using the Autoregressive Redistributive modelling on quarterly data from 1990 to 2014. Empirical results were insignificant to explain the long-run relationship between South Africa's trade, direct foreign investment and growth with the BRIC countries. The short-run trade effect was little to instil any significant effect on South Africa's growth. BRICS trade does not Granger Cause growth in South Africa. Trade and investment policy should be reviewed to correct the negative trade effect.
Keywords: F13; F43; 330; BRICS; Trade; Economic Growth; South Africa